Implantación del sistema contable en Automotriz Morales, de la ciudad de Loja, periodo julio- septiembre del 2016 - Merino Jiménez, Mariana del Cisne (2017)
This research work is carried out, as a prerequisite for obtaining the degree in Accounting and Auditing (CPA), because the relationship with society and professional practice is the academic foundation of the National University of Loja, merging the theory with the practice in the company Automotriz Morales, with the purpose of informing the owners of the real economic and financial situation of the business, giving solution to the existing problem, thus contributing to the development of the canton. The present work of thesis has its importance in the application theorypractice accounting, through concepts, definitions and categories of commercial accounting, by the system of control by permanent account; which has allowed the collection, registration and interpretation of the daily commercial activities of the Automotive Automotive Morales in order to obtain results that contribute to its owner to improve the company economically. The objectives were fulfilled through the development of the accounting process, starting with the elaboration of the Plan and Manual of Accounts according to the needs of the company, later the assets, rights and obligations of the commercial premises were identified; the merchandise inventory was managed to structure in their respective kárdex cards for which the weighted average method was applied allowing the control of the entries and exits of the articles of the commercial. In the same way, through the memorandum of operations, commercial transactions were recorded in the General Journal, General Major, Check Balance, Worksheet and finally the Economic Statements, Financial Statements, Cash Flows and the corresponding auxiliary books. Finally, with the preparation of the accounting process, information was obtained on the different economic movements of the commercial, which is why its implementation is recommended so that it has an efficient tool that allows the proper organization of the different financial resources and in this way to be able to assess its economic potential in order to correct anomalies in a timely manner.